Parental knowledge and awareness about measures taken by the dentist and attitude of parents toward bringing their children to dental hospital during the COVID-19 pandemic: A cross-sectional study - Umapathy Thimmegowda; K. Soumya Pai; Navin Hadadi Krishnamurthy; Nagarathna Chikkanarasaiah (Wolters Kluwer -Medknow Publications, 2022)
Background: In the early 2020, the world witnessed an enormous spread of coronavirus disease 2019 (COVID-19) caused by a novel coronavirus (2019-nCoV or SARS-CoV-2). It is common for parents to be frightened and their attitudes toward dental visits to change, given COVID-19's high contagion and fast spread. Aim: The aim of this study is to assess the parents' knowledge about coronavirus disease 2019 and measures taken by the dentist and to evaluate their attitudes/fears about bringing their children for dental visits during the pandemic. Materials and Methods: A structured questionnaire was developed in English and local language Kannada, which was applied to a sample of 400 parents of children aged between 4 and 12 years, of different socioeconomic backgrounds. Results: Regarding the knowledge about the COVID-19 pandemic among parents, 94% were aware about the present situation. 66% of parents perceived the dental hospital to be more dangerous when compared to public places. Regarding the attitude of parents in bringing their children to the dental clinic during the COVID-19 pandemic, 87.5% of the parents were comfortable in bringing their child to the hospital on following the COVID safety protocol. Conclusion: Majority of the parents remained well aware of the current situation about the pandemic. Patients were unlikely to take their children to the dentist except for an emergency and perceived the dental clinic as a risky place for contracting the virus. However, on providing reassuring information about infection control measures taken at the dental hospital, they were more comfortable in bringing their child to the dental hospital.